Fatwa Analysis Between National And International Fatwa Institutions On Low Molecular Weight Heparin (LMWH) As Thromboprophylaxis During Pregnancy Following Covid-19 Diagnosis - Zizi Azlinda Mohd Yusof; Nur Zaireena Zainal; Irwan Mohd Subri (Usuli Faqih Research Centre PLT, 2024)
Vol. 27 No. 2 (Page:228–245)